Mental Disorders and Oral Diseases: Future Research Directions. (January 2023) - Joury, E.; Kisely, S.; Watt, R.G.; Ahmed, N.; Morris, A.J.; Fortune, F.; Bhui, K.
The poor physical health (including oral health) of people with mental disorders is a global problem. The burden of oral diseases among this group is substantial given their high prevalence and ability to increase the personal, social, and economic impacts of mental disorders. This article summarizes causes of mental disorders and oral diseases, critically reviews current evidence on interventions to reduce the burden of oral diseases in people with mental disorders, and suggests future research directions. The relationship between mental disorders and oral diseases is complex due to the shared social determinants and bidirectional interaction mechanisms that involve interconnected social, psychological, behavioral, and biological processes. Research has, to date, failed to produce effective and scalable interventions to tackle the burden of oral diseases among people with mental disorders. Transformative research and actions informed by a dynamic involvement of biological, behavioral, and social sciences are needed to understand and tackle the complex relationship between mental disorders and oral diseases, as well as inform the design of complex interventions. Examples of future research on complex public health, health service, and social care interventions are provided. The design and testing of these interventions should be carried out in real-world settings, underpinned by the principles of coproduction and systems thinking, and conducted by a transdisciplinary team. We propose this starts with setting research priorities and developing complex intervention theory, which we report to support future research to improve oral health and hence physical and mental health in this disadvantaged group.